Synergistic upconversion and molecular imprinting in flame-made Yb/Nd co-doped TiO2 for targeted photocatalytic degradation of tetracycline in complex water - Xinhao Meng; Shuohan Wu; Zhijun Yang; Heran Zhang; Zhengliang Bian; Dongliang Zhang; Shuning Xiao; Yanjie Hu; Ying Li; Wei Bi (Environmental Research, 2026)

Self-generated microporous hydrogel coating on mesoporous silica: A hierarchical porous structure for high-performance HILIC - Shuning Li; Tong Zhang; Xiaojing Liang; Lei Wang; Yong Guo (Analytica Chimica Acta, 2026)

Fracture Evolution and Failure Mechanisms of Siltstone Mine Floors in Deep Coal Seams Under High Pore Pressure - Yuxiang Li; Shuning Dong; Xiaoming Guo (Mine Water and the Environment, 2026)

De novo generation and computational screening of dual-targeting short peptide inhibitors against PBP2b and PBP2x in drug-resistant Streptococcus Pneumoniae - Zhizhi Li; Fang Tian; Shuning Jiang; Shanshan Dong; Feifei Tian (Molecular Diversity, 2026)

Contribution of dihydroorotate dehydrogenase complex to NADH supply and metabolic flux redirection in Clostridium acetobutylicum - Dandan Jiang; Jihong Yi; Haifeng Zhu; Liangliang Gao; Shuning Wang; Guodong Liu; Lanpeng Li; Quan Zhang; Meng Wang; Armin Ehrenheich; Fuli Li; Yihua Xiao; et al. (Bioresource Technology, 2026)

Measuring and modelling of seed-applied pesticides during soybean emergence - Yang Liu; Xiangshuai Li; Fangkui Zhao; Huizhu Yuan; Xiaojing Yan; Shuning Chen; Daibin Yang (Plant and Soil, 2026)

Analysis of Rockfall Motion Characteristics Based on a 3D DDA Stochastic Model: A Case Study of the Houyu Tunnel in Fujian Province - Lu Zheng; Zhiyuan Zhu; Yihan Wu; Shuning Zhang; Zhiyuan Li; Zishuang Han; Manchao He; Guangqi Chen (Rock Mechanics and Rock Engineering, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Resveratrol synergizes with chloroquine to inhibit the malignant progression of oral squamous cell carcinoma by regulating KIF11 - Jianfeng Dong; Qing Zhu; Xuhui Fan; Shuning Li; Lin Lu; Guojie Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Tailoring the surface acidity and electronic structure of (Ce, La)PO4 via Fe modification for low-temperature NH3-SCR - Na Li; Yalin Huang; Xin Jin; Shuning Tan; Ruifang Wang; Zhiyu Zhang (Journal of Environmental Chemical Engineering, 2026)

Engineered poly (ionic liquid) hydrogel with tunable alkyl chains for multi-mode stationary phases - Shuning Li; Xiaojing Liang; Yong Guo; Shuai Wang; Licheng Wang (Analytica Chimica Acta, 2026)

Classification and Evaluation of a Shale Oil Reservoir in the Qingshankou Formation in the Southern Songliao Basin, NE China - Guofeng Wang; Dawei Zhang; Liang Yang; Yongqing Zhang; Junling He; Jilin Xing; Jun Jiang; Jijun Li; Shuning Zhang; Chenxu Yan; Hang You; Ketao Zheng; et al. (Journal of Earth Science, 2026)

The Training Effect of Tactical Awareness and Technical-Tactical Performance Among Youth Football Players: A Systematic Reviews and Meta-analysis - Jiahui Hu; Yeqin Zhang; Shuning Liu; Danyang Li; Dingmeng Ren (Journal of Science in Sport and Exercise, 2026)

Climatic suitability zoning of geographical indication Chinese jujube in Xinjiang - Xuejing Sun; Tongbin Zhao; Shuning Peng; Xiufen Li; Zhixin Hao (Theoretical and Applied Climatology, 2026)

Oil-in-water emulsions stabilized by hollow particles of zein and whey protein: Particle integrity, interfacial structure and interfacial adsorption - Kaiwen Chen; Qianqian Shen; Bohua Zhang; Shuning Zhang; Qi Fan; Gong Chen; Li Liang (Food Hydrocolloids, 2026)

Microwave-triggered plasma catalysis over Cu/CuOx wires: Synergistic CO2 reduction via enhanced discharge and dynamic oxygen vacancies - Shuning Xiao; Yang Xu; Haotong Ma; Xiuwen Zhao; Hao Zheng; Shuo Wang; Zhanshuo Tao; Hexing Li (Chemical Engineering Journal, 2026)

Binding of neonicotinoid compounds to Apis mellifera chemosensory protein 3 (AmelCSP3): Insight into the molecular toxicity of compounds with both risk and potential - Shiyu Li; Xiangshuai Li; Yang Liu; Fangkui Zhao; Daibin Yang; Li Cui; Shuning Chen; Huizhu Yuan; Xiaojing Yan (Pesticide Biochemistry and Physiology, 2025)

Evolution of phenylalanine ammonia-lyase protein family from algae to angiosperm - Chao Zhang; Huan Guo; Zhongling Li; Shuning Yue (Functional & Integrative Genomics, 2025)

Differential profiles of antibiotic resistance genes in activated sludge and biofilm in wastewater treatment plants - Haohao Sun; Weiyao Li; Shuning Zhang; Lingjue Yuan; Di Wang; Jiayue Sun; Hongyu Wang (Journal of Hazardous Materials, 2025)

Dopamine-functionalized chondroitin sulfate/gelatin-based composite hydrogels for enhancing wound healing and bone regeneration - Jian Yang; Jiale Jin; Haojie Yu; Yun Wang; Li Wang; Xiaowei Liu; Dongyu Wang; Yudi Huang; Chenguang Ouyang; Yu Wang; Yichuan Hong; Shuning Ren; et al. (Carbohydrate Polymers, 2025)

Crop rotation and organic fertilizer maintains diversity and activity of cbbL-carrying CO2-fixing bacteria in reclaimed coal mining soils - Shuning Bai; Meihua Fan; Min Wu; Xiaolong Sui; Yibo Song; Yunlong Jiang; Huisheng Meng; Yulin Liu; Xiangying Wang; Xianjun Hao; Yi Li; Jianping Hong; et al. (European Journal of Soil Biology, 2025)

Insights into the synergistic mechanisms of citric acid in detoxifying cadmium in tall fescue - Jian Cui; Wenqi Ding; Shuning Li; Xuanyang Wu; Jianing Wang; Qiuyu Su; Junxiang Qi; Xiaoyang Sun; Jinmin Fu (Journal of Hazardous Materials, 2025)

A resonance energy transfer electrochemiluminescence sensor based on the synergistic effect of luminol@β-cyclodextrin and Ni-MOF@Pt NPs for the oxytetracycline detection - Li Tian; Shuning Yang; Guangping Ma; Pengfei Han; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Dual-site Langmuir-Hinshelwood mechanism in ZnCr-LDH/NH2-UIO66 heterojunction for efficient photocatalytic NO oxidation - Jing Guo; Haotong Ma; Huan Shang; Wenchao Wang; Ruiyi Yang; Shuo Wang; Yingchun Miao; David Lee Phillips; Guisheng Li; Shuning Xiao (Journal of Hazardous Materials, 2025)

Production of fucose-rich exopolysaccharides by UV-mutated Enterobacter: Optimization, structural characterization and functional properties - Zhemin Li; Shuning Ren; Xiufang Bi; Dan Shu; Di Luo; Jie Yang; Xin Li (Food Bioscience, 2025)

Keystone ecological cluster rather than the whole community of phoD-encoding bacteria driving ecological function and the improvement of yield under long-term organic regime in greenhouse - Xiaoxia Li; Pengjie Li; Muhammad Awais; Zhu Zhang; Shuning Zhao; Yufeng Liu; Zhouping Sun; Hongdan Fu; Tianlai Li (Agriculture, Ecosystems & Environment, 2025)

Solid-state electrochemiluminescence sensor based on TiO2@CdSe and Ru(bpy)32+@Ag NPs for ultrasensitive detection of malathion - Huiling Li; Li Tian; Shuning Yang; Chao Li; Ruidan Li; Yujia Song; Yanjia Guo; Xuwen Li (Food Chemistry, 2025)

Redox processes at the slab-mantle interface: Evidence from reduced carbon inclusions in mantle wedge peridotites - Yi Su; Shuning Li; Ren-Xu Chen; Yong-Fei Zheng (Earth and Planetary Science Letters, 2025)

Development of a Colloidal Gold Immunochromatographic Strip for Specific Detection of Photobacterium damselae subsp. piscicida - Shuning Zhang; Jianbai Zhang; Yan Gao; Dandan Zhou; Binzhe Zhang; Xuepeng Li; Jian Zhang (Journal of Fish Diseases, 2025)
Photobacterium damselae subsp. piscicida (Pdp) is characterised by high infectivity and mortality and wide distribution, resulting in substantial economic losses to the global aquaculture industry. Therefore, it is critical to develop a simple, rapid and accurate diagnostic method for Pdp detection. Herein, two Pdp‐specific monoclonal antibodies (mAbs 1H7 and 6E6) were obtained, indirect enzyme‐linked immunosorbent assay and immunofluorescence analysis confirmed that the mAbs specifically recognised the outer membrane of Pdp but could not recognise the other Gram‐positive or Gram‐negative bacteria, indicating good specificity. A colloidal gold immunochromatographic strip (CGICS) was developed here for Pdp detection by optimising the colloidal gold labeling and antibody coating conditions using 1H7 as a colloidal gold‐labelled antibody and 6E6 as a coated antibody. The CGICS exhibited a detection limit of 1 × 10 5 CFU/mL for Pdp and a detection time of 10 min. Cross‐reaction analysis revealed that the CGICS could specifically detect different Pdp isolates without cross‐reaction with the other bacterial species or the subspecies P. damselae subsp . damselae . Stability analysis revealed that the CGICS were stored in closed plastic packaging at 25°C and 4°C for more than 8 months. The CGICS retained their detection limit after 6 months at 4°C, and 4 months at 25°C. Using tissues from the experimentally challenged Lateolabrax maculatus , the CGICS and polymerase chain reaction revealed a 100% coincidence rate. These findings indicated that the established CGICS exhibits high specificity and sensitivity. It is rapid and simple for Pdp detection, making it a potential on‐site tool for Pdp detection in fish aquaculture.

Heavy metals migration and in-situ solidification in the co-combustion of solid waste fuels: Rules and differences - Shuning Qin; Li Jia; Xiaolei Qiao; Chenxing Wang; Baihe Guo; Xinyue Chang; Peng Cheng; Yan Jin (Journal of Environmental Chemical Engineering, 2025)

Establishment and application of a duplex fluorescent quantitative PCR assay for H9N2 subtype avian influenza virus and infectious bronchitis virus - Wanting Zhou; Qiuyan Mao; Shuning Zhou; Tingting Li; Jie Tian; Xiaoqi Li; Shuo Liu; Cheng Peng; Zhibin Hu; Jinping Li; Guangyu Hou; Houhui Song; et al. (Virus Genes, 2025)

Gonyaulax montresoriae sp. nov. (Dinophyceae) from the Adriatic Sea produces predominantly yessotoxin - Shuning Huang; Kenneth Neil Mertens; Amélie Derrien; Ophélie David; Hyeon Ho Shin; Zhun Li; Xiuyun Cao; Marina Cabrini; Daniela Klisarova; Haifeng Gu (Harmful Algae, 2025)

High-efficiency PMS activation by difunctional Co-Fe PBA/g-C3N4 S-scheme heterojunction for oxytetracycline degradation: Performance evaluation and mechanism insight - Junjie Chen; Shuning Yu; Xialiang Jiang; Cheng Chen; Liguo Shen; Renjie Li; Yanchao Xu; Mingzhu Zhou; Bisheng Li; Honjun Lin (Science of The Total Environment, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Study on regeneration mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Yan Jin; Shuning Qin (Science of The Total Environment, 2024)

Synthesis of ultrafine Mo2N particles supported on N doped carbon material for guaiacol hydrodeoxygenation - Chenglong Wen; Shuning Li; Peng Zhang; Mohong Lu; Jie Zhu; Mingshi Li; Chunshan Song (Biomass and Bioenergy, 2024)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

How did submarine volcanic eruptions interact with organic matter to favour hydrocarbon generation in the Bohai Bay Basin, China? - Chuanming Li; Jianhui Zeng; Shuning Liu; Yuyang Dong; Maoyun Wang (International Geology Review, 2024)

Micro-transcriptome analysis reveals miRNA-mediated survival strategies between megalocytivirus RBIV-C1 and Scophthalmus maximus - Jian Zhang; Xiangyi Sun; Shuning Zhang; Xuepeng Li (Aquaculture, 2024)

Utilization of γ-polyglutamic acid/pectin hydrogel with 1-MCP on the apricot storage - Shuning Yang; Jinfeng Zhang; Xiaopei Hu; Suhong Li; Tuoping Li (Journal of Stored Products Research, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

The synergistic nucleation of iodous acid and sulfuric acid: A vital mechanism in polluted marine regions - Haotian Zu; Shaobing Zhang; Shuning Li; Ling Liu; Xiuhui Zhang (Atmospheric Environment, 2024)

An electrochemiluminescence sensor based on the CNTs and CdSe@ZnSe for determination of melamine in milk samples - Qian Wu; Li Tian; Xiangyu Shan; Huiling Li; Shuning Yang; Chao Li; Juan Lu (Food Chemistry, 2024)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Interference of periostin attenuates pathological changes, proinflammatory markers and renal fibrosis in diabetic kidney injury - Xiaoting Duan; Cheng Chen; Xiaoli Liu; Taoxia Wang; Shuning Feng; Jianwei Li; Guiying Li (Genes & Genomics, 2023)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Intelligent real-time identification technology of stratum characteristics during slurry TBM tunneling - Yingran Fang; Xinggao Li; Hongzhi Liu; Shuning Hao; Yang Yi; Yidong Guo; Hanyuan Li (Tunnelling and Underground Space Technology, 2023)

A bibliometric review on electric vehicle (EV) energy efficiency and emission effect research - Shengyong Yao; Zixiang Bian; Mohammad Kamrul Hasan; Ru Ding; Shuning Li; Yanfei Wang; Shulei Song (Environmental Science and Pollution Research, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices - Zhuo Sun; Juan Lu; Xin Zhang; Xiangyu Shan; Qian Wu; Chao Li; Huiling Li; Shuning Yang; Li Tian (Food Chemistry, 2023)

Unexpectedly significant stabilizing mechanism of iodous acid on iodic acid nucleation under different atmospheric conditions - Ling Liu; Shuning Li; Haotian Zu; Xiuhui Zhang (Science of The Total Environment, 2023)

Photo-sonodynamic therapy mediated with OLI_NPs to induce HPV16E7-specific immune response and inhibit cervical cancer in a Tc-1-grafted murine model - Guangzong Zhao; Shuning Chen; Jiao Zheng; Chenyang Li; Xiaowen Zhong; Yang Cao; Yue Zheng; Jiangchuan Sun; Shenyin Zhu; Shufang Chang (Journal of Photochemistry and Photobiology B: Biology, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

Dynamic Characteristics of Water Inflow from a Coal Mine’s Roof Aquifer - Zhenfang Zhou; Shuning Dong; Hao Wang; Dewu Jin; Xiaodong Wang; Yang Dong; Shi Chen; Debin Li; Xingling Dong; Hongbo Shang (Mine Water and the Environment, 2022)

A quadruple recombination event discovered in hepatitis E virus - Hao Shen; Shuning Liu; Min Ding; Haixia Gu; Ming Chang; Yanshuang Li; Hua Wang; Xingwen Bai; Hongxing Shen (Archives of Virology, 2021)

Prevention and Control of Water Inrushes from Subseam Karstic Ordovician Limestone During Coal Mining Above Ultra-thin Aquitards - Xiaolong Li; Shuning Dong; Kaide Liu (Mine Water and the Environment, 2021)

Mine Water Source Discrimination Based on Hydrogeochemical Characteristics in the Northern Ordos Basin, China - Jian Yang; Shuning Dong; Hao Wang; Guoqing Li; Tiantian Wang; Qiangmin Wang (Mine Water and the Environment, 2021)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Saponins as modulators of nuclear receptors - Tiehua Zhang; Shuning Zhong; Tiezhu Li; Jie Zhang (Critical Reviews in Food Science and Nutrition, 2020)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

The scale dependence of dispersivity in multi-facies heterogeneous formations - Shuning Dong; Zhenxue Dai; Jingsheng Li; Wanfang Zhou (Carbonates and Evaporites, 2018)

Estrogenicity of halogenated bisphenol A: in vitro and in silico investigations - Jie Zhang; Tiezhu Li; Tuoyi Wang; Cuiping Yuan; Shuning Zhong; Tianzhu Guan; Zhuolin Li; Yongzhi Wang; Hansong Yu; Quan Luo; Yongjun Wang; Tiehua Zhang (Archives of Toxicology, 2018)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)

Radiation-Induced Bystander Effects in A549 Cells Exposed to 6 MV X-rays - Shuning Yang; Jing Xu; Weixian Shao; Chong Geng; Jia Li; Feng Guo; Hui Miao; Wenbin Shen; Tao Ye; Yazhou Liu; Haiting Xu; Xuguang Zhang (Cell Biochemistry and Biophysics, 2015)

Instability in mitochondrial membranes in Polima cytoplasmic male sterility of Brassica rapa ssp. chinensis - Ying Li; Tongkun Liu; Weike Duan; Xiaoming Song; Gongjun Shi; Jingyi Zhang; Xiaohui Deng; Shuning Zhang; Xilin Hou (Functional & Integrative Genomics, 2014)

A cDNA Clone of BcHSP81-4 from the Sterility Line (Pol CMS) of Non-heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Tongkun Liu; Xilin Hou; Jingyi Zhang; Yuping Song; Shuning Zhang; Ying Li (Plant Molecular Biology Reporter, 2011)